The implementation of new eSocial rules and the adaptation of accounting professionals (Revista Brasileira de Contabilidade e Gestão, 2022)
eSocial emerged from the publication of Federal Decree n.º 8.373/2014, in which the Federal Government sought to facilitate the collection of data from companies in their accounting sectors and personnel department. The changes arising from eSocial implied changes in the routines of accounting professionals. In this sense, the objective of the present study is to investigate how accounting professionals are adapting to the changes brought by eSocial version S-1.0. The research was carried out with accounting professionals who work in the personal department of accounting offices in the city of Guarapuava/PR. Based on descriptive statistics, the data were analyzed, and the findings indicate that professionals are adapting to the changes brought by eSocial, in addition to observing great advantages in its implementation.
Keywords: eSocial; accounting professionals; implantation; new eSocial rules; Federal Decree n. 8,373/2014; accounting professional routines